1996
DOI: 10.1148/radiology.199.1.8633133
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity pneumonitis: correlation of individual CT patterns with functional abnormalities.

Abstract: Areas of decreased attenuation and mosaic perfusion are an important ancillary CT finding in hypersensitivity pneumonitis, and obstructive functional abnormalities indicate that this phenomenon is caused by bronchiolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
2
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(102 citation statements)
references
References 0 publications
3
90
2
7
Order By: Relevance
“…Although the identification of emphysema in the presence of interstitial fibrosis is controversial [138], it is possible that areas of emphysema occur interspersed among pulmonary fibrosis in chronic cases of hypersensitivity pneumonitis. Nevertheless, in a study of patients with subacute, but not chronic, extrinsic allergic alveolitis, multivariate analysis showed that there was no independent relationship between the extent of decreased attenuation on CT and DL,CO; but there was a relationship with RV/TLC, which would favour bronchiolitis, rather than emphysema, as the cause of areas of decreased attenuation [134].…”
Section: Miscellaneous Conditions With Small Airways Involvementmentioning
confidence: 93%
See 1 more Smart Citation
“…Although the identification of emphysema in the presence of interstitial fibrosis is controversial [138], it is possible that areas of emphysema occur interspersed among pulmonary fibrosis in chronic cases of hypersensitivity pneumonitis. Nevertheless, in a study of patients with subacute, but not chronic, extrinsic allergic alveolitis, multivariate analysis showed that there was no independent relationship between the extent of decreased attenuation on CT and DL,CO; but there was a relationship with RV/TLC, which would favour bronchiolitis, rather than emphysema, as the cause of areas of decreased attenuation [134].…”
Section: Miscellaneous Conditions With Small Airways Involvementmentioning
confidence: 93%
“…14); these patterns reflect lymphocytic interstitial pneumonitis, peribronchiolar exudate, and bronchiolitis respectively. There is a strong correlation between the extent of the areas of decreased attenuation (a component of the mosaic attenuation pattern) on HRCT and pulmonary function indices of air-trapping [134,135]. The airtrapping, graphically shown on expiratory CT, is present in the great majority of patients with subacute disease, and reflects the underlying component of bronchiolitis.…”
Section: Miscellaneous Conditions With Small Airways Involvementmentioning
confidence: 99%
“…Honeycombing, which is a requirement for a diagnosis of UIP/IPF, has been reported in 16% to 69% of CHP cases, 12,15,16 and in contrast to the honeycombing in patients with UIP/IPF, honeycombing in patients with CHP seldom has a basal predominance. The reticulation in CHP can be patchy, random or peribronchovascular or have a predominantly subpleural distribution, mimicking UIP/IPF.…”
mentioning
confidence: 99%
“…Lobular areas of decreased attenuation and vascularity ( Figure 1, E and F) are described in approximately 80% of patients, with poorly defined centrilobular nodules in approximately 50% of patients. 12,[16][17][18][19][20][21] In contrast, UIP/IPF shows reticulation in all lobes; no or minimal ground-glass opacities; honeycombing, which is often extensive; and a peripheral and basal distribution. 12 However, as noted, these criteria fail to provide separation in 50% of cases; in particular, there can be considerable overlap between CHP and UIP/IPF.…”
mentioning
confidence: 99%
“…59 Their extension correlates with severity of air trapping, as indicated by an increased residual volume. 60 When air-trapping areas, ground-glass opacities, and normal lung are seen at the same HRCT section, the pattern is called "headcheese sign". The CT imaging pattern is reminiscent of the variegated appearance of headcheese cold cut meat.…”
Section: Pereira Et Almentioning
confidence: 99%